2004
DOI: 10.1016/s0004-9514(14)60152-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and laser therapy in the treatment of carpal tunnel syndrome

Abstract: This study was designed to compare the efficacy of ultrasound and laser treatment for mild to moderate idiopathic carpal tunnel syndrome. Ninety hands in 50 consecutive patients with carpal tunnel syndrome confirmed by electromyography were allocated randomly in two experimental groups. One group received ultrasound therapy and the other group received low level laser therapy. Ultrasound treatment (1 MHz, 1.0 W/cm(2), pulse 1:4, 15 min/session) and low level laser therapy (9 joules, 830 nm infrared laser at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 25 publications
8
72
0
10
Order By: Relevance
“…KD grubundaki artışın KKD grubuna göre anlamlı oranda daha fazla olması, bize bu etkinin KD tedavisinin yumuşak dokulardaki derin ısıtıcı etkilerine bağlı olabileceğini düşündürmüştür. Nitekim, yine bir derin ısıtıcı olan ultrason tedavisi ile yapılmış çalışmalarda, KTS semptom şiddeti ve fonksiyonel skorlarında, ağrı skorlarında ve el kavrama ve parmak sıkma gücünde plaseboya oranla anlamlı düzelmeler saptanmıştır (26,27). Araştırmacılar bu etkiyi US'nin derin ısıtıcı etkilerinden dolayı dokularda meydana gelen kan akımında artış, lokal metabolizmada artış ve bunların sonucu olan doku rejenerasyonunda artışa bağlamışlar, aynı zamanda ağrı ve inflamasyonu azaltıcı etkilerin sinir rejenerasyonunu kolaylaştıracağının altını çizmişlerdir (26,27).…”
Section: Discussionunclassified
“…KD grubundaki artışın KKD grubuna göre anlamlı oranda daha fazla olması, bize bu etkinin KD tedavisinin yumuşak dokulardaki derin ısıtıcı etkilerine bağlı olabileceğini düşündürmüştür. Nitekim, yine bir derin ısıtıcı olan ultrason tedavisi ile yapılmış çalışmalarda, KTS semptom şiddeti ve fonksiyonel skorlarında, ağrı skorlarında ve el kavrama ve parmak sıkma gücünde plaseboya oranla anlamlı düzelmeler saptanmıştır (26,27). Araştırmacılar bu etkiyi US'nin derin ısıtıcı etkilerinden dolayı dokularda meydana gelen kan akımında artış, lokal metabolizmada artış ve bunların sonucu olan doku rejenerasyonunda artışa bağlamışlar, aynı zamanda ağrı ve inflamasyonu azaltıcı etkilerin sinir rejenerasyonunu kolaylaştıracağının altını çizmişlerdir (26,27).…”
Section: Discussionunclassified
“…Thus, the laser energy might be absorbed by the soft tissue, and insufficient energy reaches the injured nerve. Bakhtiary and Rashidy-Pour tried to use an 830 nm point-like LLLT (1.8 J / point) to irradiate 5 points on the distribution of median nerve 9) , and they obtained an unsuccessful result. The reason was that the nerve dispersion is different from each patient, and this method is very hard to provide an appropriate dosage for the injured section of the nerve 21) .…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of LLLT in treating CTS is controversial. The beam energy of LLLT was more than 9 J in studies [6][7][8] which found the treatment to be effective, while the energy was less than 6 J in a study which found it ineffective 9) . Besides, regarding pain, there are several reports of the effectiveness of LLLT on physiological factors and it has been shown to be an effective treatment by meta-analysis 3,5) .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is suggested that ultrasound therapy may accelerate the healing process in damaged tissues. 24 It is often prescribed along with nerve and tendon exercises. The AAOS guideline recommends ultrasound treatment of CTS.…”
Section: Ultrasoundmentioning
confidence: 99%